1997
DOI: 10.1093/oxfordjournals.aje.a009110
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Caffeine Intake During Pregnancy on Birth Weight

Abstract: The aim of this study was to examine the effect of caffeine consumption during pregnancy on birth weight and its possible interaction with smoking. The sample included 1,011 women who were interviewed during their first 3 days after delivery in one of the hospitals of Belgrade, Yugoslavia. A significant reduction in birth weight was found to be associated with an average caffeine intake of > or = 71 mg per day, after adjustment for gestational age, infant sex, parity, and maternal height and weight, but only i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
1
15

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 10 publications
2
37
1
15
Order By: Relevance
“…In some studies, the effect was confined to subgroups of the studied population. Thus, Beaulac-Baillargeon and Desrosier (1987) and Peacock et al (1991) observed a foetal growth retardation at high caffeine intakes only in smokers, while Vlajinac et al (1997) found an association only in non-smokers. In two retrospective studies (Fenster et al, 1991;Fortier et al, 1993) a significant effect could be seen only on intrauterine growth retardation, whereas low birth weight, which was also measured, was unaffected.…”
Section: Caffeinementioning
confidence: 94%
See 3 more Smart Citations
“…In some studies, the effect was confined to subgroups of the studied population. Thus, Beaulac-Baillargeon and Desrosier (1987) and Peacock et al (1991) observed a foetal growth retardation at high caffeine intakes only in smokers, while Vlajinac et al (1997) found an association only in non-smokers. In two retrospective studies (Fenster et al, 1991;Fortier et al, 1993) a significant effect could be seen only on intrauterine growth retardation, whereas low birth weight, which was also measured, was unaffected.…”
Section: Caffeinementioning
confidence: 94%
“…Eight out of the nineteen studies designed to investigate a potential relationship between caffeine exposure and foetal growth retardation observed a statistically significant relationship between the exposure and the studied endpoint (Kuzma and Sokol, 1982;Watkinson and Fried, 1984;Beaulac-Baillargeon and Desrosiers, 1987;Martin and Bracken, 1987;Peacock et al, 1991;Fenster et al, 1991b;Fortier et al, 1993;Vlajinac et al, 1997). In four of these studies (Martin and Bracken, 1987;Fenster et al, 1991b;Fortier et al, 1993;Vlajinac et al, 1997) a dose response relationship was observed.…”
Section: Caffeinementioning
confidence: 95%
See 2 more Smart Citations
“…Some studies conducted on the effect of caffeine intake in pregnancy and the risk of small for gestational age (SGA) have shown an increased risk (Vlajinac et al, 1997;Fernandes et al, 1998), particularly in women drinking three or more cups of coffee per day (Warkinson & Fried, 1985;Martin & Bracken, 1987;Cann & Goldhaber, 1989;Olsen et al, 1991;Eskenazi et al, 1999;Bracken et al, 2003), but others did not find any association (Peacock et al, 1991;Shu et al, 1995;Grosso et al, 2001;Clausson et al, 2002). Most studies did not take into account the confounding effects of smoking and alcohol intake and nausea in pregnancy (Dlugosz & Bracken, 1992;Mills et al, 1993;Shiono & Klebanoff, 1993;Fernandes et al, 1998).…”
Section: Introductionmentioning
confidence: 99%